Disalgnment of Railroad Poles as Dynamic Effect of Rolling Stock. (2016) - Kudryavtsev, Sergey; Maleev, Dmitri; Tsvigunov, Dmitri; Goncharova, Elena
Abstract: The paper covers the results of the research into railroad pole deformations being a part of the railway embankment. The research investigates a dynamic impact of the rolling stock by the seismic sounding of "rolling stock- embankment - railroad pole" system to receive a qualitative assessment of vibrations spreading in railroad poles.